WEWENANG PEMERINTAH DAERAH DALAM PEMBERIAN IZIN LINGKUNGAN HIDUP - Vica J. E. Saija (Faculty of Law, Universitas Pattimura, 2014)
The results showed that local governments have the authority to give a license for environmental management based on the Chapter 237 Law Number 32 of 2004 Concerning the Local Government Jo Chapter 63 Law Number 32 of 2009 on Environmental Protection and Management, verse (2) letter r and verse (3) letter o. As a holder of the delegation, the local government then have the authority to issue permits and enforce the law on consent in the form of monitoring and enforcing sanctions. Licensing authority for environmental management by local governments in its implementation was not maximized yet, this is due to the Law Number 32 of 2009 on Environmental Protection and Management, which does not have implementing regulations, the rule of umbrella act is to set the basic terms only, that contributes to there was no concrete licensing division of the authorized government, both at the central and regional. Therefore, it is the authority of government including local government (Ministers, Governors, Regents/Mayors) should be based on the criteria of externality, accountability, and efficiency. And recommended that the licensing authority for environment management, in its implementation, should be based on the principle of Good Licensing Governance on Based Natural Resources, in order to prevent abuse of authority and to simplify the licensing process. The Law Number 32 of 2009 it is implementation, it still needs to be followed up with any implementing regulation in order to run as it is expected.